ROLE OF MAGNETIC RESONANCE IMAGING IN EVALUATION OF UTERINE PATHOLOGIES AND ITS CORRELATION WITH ULTRASOUND - AAYUSH BANSAL; SIMMI BHATNAGAR; MANOJ MATHUR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Uterine pathologies, both benign and malignant, are common among reproductive age females and postmenopausal females. Herein, we aim to assess the role of magnetic resonance imaging (MRI) in the evaluation of uterine pathologies and to correlate them with ultrasonographic findings (USG). Methods: We conducted a prospective study in the Department of Radiodiagnosis at Government Medical College and Rajindra Hospital, Patiala. It included 45 females who were referred from department of obstetrics and gynecology with clinical suspicion of uterine pathologies. All the patients underwent both USG and MRI, results were compiled and statistical tests applied. Results: The mean (±SD) age of patients was 38.9±10.8 years. About 82% of the females were premenopausal. Nineteen females were diagnosed with fibroids, nine had adenomyosis, and two patients had endometrial polyps. Five of each were histopathologically proven cases of cervical and endometrial carcinoma. Four patients were diagnosed with Mullerian anomalies. MRI could diagnose more number of fibroids and in more number of patients. On USG, adenomyosis was falsely diagnosed in one patient and was reported as normal in one other patient. In cases of endometrial carcinoma, myometrial invasion was better predicted through MRI. Similarly, in cases of cervical carcinoma, parametrial extension was underdiagnosed by USG alone. MRI detected bicornuate bicollis uterus and septate uterus in two cases each. Very good correlation was observed between the USG and MRI findings with Kappa coefficient of 0.823 (p<0.001). Conclusion: MRI is the radiological imaging of choice in patients with suspected uterine pathologies and correlates well with USG. Therefore, USG and MRI should be combined together in case of diagnostic dilemma for better decision-making and patient management